The Effect of Risk Perception, Financial Self-Efficacy, Brand Image, Moslem Celebrity Endorsers, and Sharia Compliance on Gen Z Gold Investment Decisions in Sharia Financial Institutions - Umi Khozinatul Khoiriyah; Faizal Amir (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the influence of risk perception, financial self-efficacy, brand image, Muslim celebrity endorsers, and sharia compliance on Generation Z gold investment decisions in Islamic financial institutions. Using a quantitative approach and data collected through a survey of 150 Generation Z respondents who invest in Islamic gold, this study tested the hypothesis using multiple linear regression analysis. The results showed that risk perception, financial self-efficacy, brand image, and sharia compliance had a positive and significant effect on Generation Z gold investment decisions, while Muslim celebrity endorsers did not have a significant effect. Simultaneously, all five variables had a significant effect. These findings imply that Islamic financial institutions need to consider these factors in designing marketing strategies and investment products that suit Generation Z preferences. Sharia compliance is a key factor in attracting Generation Z investors, so financial institutions need to emphasize their commitment to sharia principles.